A performance evaluation of smart beta exchange traded funds. (6th December 2019) - Rompotis, Gerasimos G.
The focus of this paper is on smart beta ETFs, which promise enhanced returns to investors. The ability of smart beta ETFs to beat the market and offer material excess returns is investigated along with the impact on performance by various market factors such as size, value and profitability. The relation of returns, pricing discrepancy and volatility is assessed too. Moreover, the ability of ETFs to time the market is evaluated along with their efficiency in replicating the performance of their benchmarks. Finally, a market trend analysis examines how smart beta ETFs respond to the upswings and downfalls of the stock market. Results reveal that smart beta ETFs cannot outperform the market. Moreover, the influence of market factors on ETF performance is modest whereas performance is significantly related to contemporaneous and lagged premiums and intraday volatility. On the timing skills of ETF managers, the results show that they luck in such skills. In addition, the tracking error of ETFs is significant. Finally, the market trend analysis indicates that smart beta ETFs are not absolutely aligned with the overall stock market, that is, to a significant degree, ETFs move contrary to the ascending or descending paths of the market.